Left Atrial Appendage Opacification on Cardiac Computed Tomography in Acute Ischemic Stroke: The Clinical Implications of Slow‐Flow - Shan Sui Nio; Leon A. Rinkel; Olivia N. Cramer; Z. Beyda Özata; Chiel F. P. Beemsterboer; Valeria Guglielmi; Berto J. Bouma; S. Matthijs Boekholdt; Nick H. J. Lobé; Ludo F. M. Beenen; Henk A. Marquering; Charles B. L. M. Majoie; et al. (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease)
Background Left atrial appendage (LAA) slow‐flow may increase the risk of ischemic stroke. We studied LAA attenuation on cardiac computed tomography in patients with acute ischemic stroke. Methods and Results We used data from a prospective cohort of patients with acute ischemic stroke undergoing cardiac computed tomography during the acute stroke imaging protocol. We compared characteristics, functional outcome (modified Rankin scale: higher scores indicating worse outcome), stroke recurrence and major adverse cardiovascular events after 2‐year follow‐up between patients with LAA thrombus (filling defect<100 Hounsfield Unit (HU)), slow‐flow (filling defect ≥100 HU) and normal filling. Of 421 patients, 31 (7%) had LAA thrombus, 69 (16%) slow‐flow, and 321 (76%) normal filling. Patients with thrombus or slow‐flow more often had known atrial fibrillation compared with normal filling (45%, 39%, and 9%, P<0.001). Patients with thrombus had higher National Institutes of Health Stroke Scale‐scores compared with slow‐flow and normal filling (18 [interquartile range, 9–22], 6 [interquartile range, 3–17], and 5 [interquartile range, 2–11], P<0.001). Compared with normal filling, there was no difference with slow‐flow in functional outcome (median modified Rankin scale, 3 versus 2; acOR 0.8 [95% CI, 0.5–1.4]), stroke recurrence (adjusted hazard ratio, 0.8 [95% CI, 0.3–1.9]) or major adverse cardiovascular events (adjusted hazard ratio, 1.2 [95% CI, 0.7–2.1]), while patients with thrombus had worse functional outcome (median modified Rankin scale, 6, acOR, 3.3 [95% CI, 1.5–7.4]). In cryptogenic stroke patients (n=156) slow‐flow was associated with stroke recurrence (27% versus 6%, aHR, 4.1 [95% CI, 1.1–15.7]). Conclusions Patients with slow‐flow had similar characteristics to patients with thrombus, but had less severe strokes. Slow‐flow was not significantly associated with functional outcome or major adverse cardiovascular events, but was associated with recurrent stroke in patients with cryptogenic stroke.